Modern Climate and Soil Properties Explain Functional Structure Better Than Phylogenetic Structure of Plant Communities in Northern China - Shi, Yabo; Su, Chuang; Wang, Mingchen; Liu, Xinliang; Liang, Cunzhu; Zhao, Liqing; Zhang, Xinyu; Minggagud, Hugjiltu; Feng, Gang; Ma, Wenhong (Frontiers in Ecology and Evolution, 2020)
Mechanisms of plant community assembly at geographical scale are an interesting topic in ecology and biogeography, which are of great significance for the understanding of species coexistence and biodiversity conservation. But so far, only a few studies have simultaneously assessed the relative roles of multiple-scale factors in shaping phylogenetic and functional structure of plant communities at a macroecological scale. In this study, we linked modern climate, glacial-interglacial climate change and soil properties with phylogenetic and functional structure of shrub and herbaceous plant communities in Inner Mongolia, China, an arid and semi-arid region. Our results showed that functional structure of plant communities was more associated with modern climate and soil properties than phylogenetic structure, especially for the soil properties. Modern precipitation was found in all the combinations of variables that were most closely related to the community structure in this arid and semi-arid region. These findings suggest that phylogenetic and functional structure of biotic communities may be affected by processes at divergent spatial-temporal scales. That is, functional structure is better linked with modern and local factors, while phylogenetic structure is more associated with historical and 2 regional processes. This study highlights the importance of the associations between different biodiversity dimensions and divergent drivers.